Righting her-story : Caribbean women encounter the Bible story - Sheerattan-Bisnauth, Patricia,ed.; World Communin of Reformed Churches (Geneva : World Communion of Reformed Churches, 2011)
Righting her-story: Caribbean women encounter the Bible story is a Bible study book on women which provides refreshing ways to read the Bible, enabling women and men to rediscover its richness and its ability to help them reflect theologically on their faith and experience. It has twenty Bible studies with stories of women, a Bible study training guide, poems and liturgies. A variety of popular approaches and methodologies for contextual Bible study is used. It is an exciting journey of discovering new insights and ways of reading the Bible from a gender lens with a critical consciousness of one's contextual reality. The book serves as an instrument for transformative education, conscientization and enabling change. (back cover).
A service to celebrate emancipation / Robina Marie Winbush.
"April 2011" -- T.p. verso
Includes bibliographical references (p. 260-263)
Keywords: Bible -- Feminist criticism; Bible -- Criticism, interpretation, etc